Angiopoietins 1 and 2 in sputum supernatant of optimally treated asthmatics: the effect of smoking. (January 2015) - Petta, Vasiliki; Bakakos, Petros; Tseliou, Eleni; Kostikas, Konstantinos; Simoes, Davina C. M.; Konstantellou, Elissavet; Hillas, Georgios; Koulouris, Nikolaos G.; Papiris, Spyros; Loukides, Stelios
Abstract Background Angiopoietin‐1 (Ang‐1) is an essential mediator of angiogenesis by establishing vascular integrity, whereas angiopoietin‐2 (Ang‐2) acts as its natural inhibitor. Objective We aimed to determine the levels of angiopoietins in sputum supernatants of patients with optimally treated asthma and to investigate whether smoking represents a significant covariate on the above possible processes. Methods Eighty‐seven patients with asthma (42 smokers) and 28 healthy subjects (14 smokers) were studied. All subjects underwent lung function tests, bronchial hyper‐responsiveness assessment and sputum induction for cell count identification and measurement of Ang‐1, Ang‐2, vascular endothelial growth factor, TGF‐β1, MMP‐2, IL‐13, Eosinophilic cationic protein and IL‐8 in supernatants. Airway vascular permeability (AVP) index was also assessed. Results Ang‐1 (ng/mL) levels were significantly higher in patients with asthma compared to normal subjects. Smoking significantly increased Ang‐1 levels [median, interquartile ranges 24 (13–37) in smoking asthmatics vs 10 (7–14) in nonsmoking asthmatics vs 5·3 (3·7–6·5) and 4·6 (3·8–5·7) in healthy smokers and nonsmokers, respectively, P < 0·001]. Similar results were observed for Ang‐2 (pg/mL) [168 (132–203) vs 124 (82–152) vs 94 (78–113) vs 100 (96–108), respectively, P < 0·001]. Regression analysis in the whole study population showed a significant negative association for Ang‐1, with AVP index, and MMP‐2. Smoking was a significant covariate for both Ang‐1 and Ang‐2 in asthmatic patients. Conclusions Ang‐1 and Ang‐2 levels are upregulated in patients with optimally treated asthma. Our data support a possible role for smoking in the angiogenetic process in asthma.